2011
DOI: 10.1128/jvi.06093-11
|View full text |Cite
|
Sign up to set email alerts
|

A Murine Genital-Challenge Model Is a Sensitive Measure of Protective Antibodies against Human Papillomavirus Infection

Abstract: The available virus-like particle (VLP)-based prophylactic vaccines against specific human papillomavirus (HPV) types afford close to 100% protection against the type-associated lesions and disease. Based on papillomavirus animal models, it is likely that protection against genital lesions in humans is mediated by HPV type-restricted neutralizing antibodies that transudate or exudate at the sites of genital infection. However, a correlate of protection was not established in the clinical trials because few dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
74
3
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(84 citation statements)
references
References 33 publications
(34 reference statements)
6
74
3
1
Order By: Relevance
“…Transfer of 2 l of serum resulted in intermediate in vivo protection (35% to 89%) and in vitro titers from 154 to 228. In vitro titers were below the limit of detection for 4/5 animals at the 0.2-l dose, whereas 3 animals were partially protected in vivo (16,23, and 70% protection). Therefore, the in vivo assay may still be slightly more sensitive when considering serum concentrations that offer a lower level of protection.…”
Section: Fig 4 In Vivo Protection and Correlation With In Vitro Neutrmentioning
confidence: 89%
See 1 more Smart Citation
“…Transfer of 2 l of serum resulted in intermediate in vivo protection (35% to 89%) and in vitro titers from 154 to 228. In vitro titers were below the limit of detection for 4/5 animals at the 0.2-l dose, whereas 3 animals were partially protected in vivo (16,23, and 70% protection). Therefore, the in vivo assay may still be slightly more sensitive when considering serum concentrations that offer a lower level of protection.…”
Section: Fig 4 In Vivo Protection and Correlation With In Vitro Neutrmentioning
confidence: 89%
“…A recent mouse study identified substantial differences in the relative sensitivities of the in vivo genital HPV challenge assay and the standard L1-based in vitro assay as measures of protective L1 antibodies (23). These authors demonstrated that the in vivo detection of protection was slightly more sensitive (30-fold) than the in vitro assay for a murine L1-specific monoclonal antibody.…”
Section: Fig 4 In Vivo Protection and Correlation With In Vitro Neutrmentioning
confidence: 99%
“…This may be because protection of the vaccine is provided through the production of serum neutralizing anti-HPV IgG antibodies binding to viral particles, [17][18][19] which only requires small amounts of antibody to be present. 20,21 One interesting finding was that vaccinated young adult women had a higher prevalence than unvaccinated women of www.tandfonline.comhigh-risk types other than HPV 16 and 18, and thus are still at risk of cervical cancer and other HPV-related cancers. This is consistent with clinical trials on the quadrivalent vaccine which showed it provided some protection against HPV 31 and 59, but not other types.…”
Section: Discussionmentioning
confidence: 99%
“…Details about NHANES can be found elsewhere. 27 Our study included young adult women (20)(21)(22)(23)(24)(25)(26) was first approved for use in 2006, all women in this age range would have received the vaccine after 12 years of age. This age group was selected because few data are available on those vaccinated after the recommended age of 11-12 years.…”
Section: Methodsmentioning
confidence: 99%
“…While a passive transfer of immune serum clearly demonstrates the presence of neutralizing antibodies, a challenge of an immunized animal is less clear as immune mechanisms other than antibodies may be mediating protection. Of note, Longet and colleagues already demonstrated that passive transfer of mouse L1 VLP (Gardasil) immune sera >100-fold lower (in titer) than those detectable by standard in vitro neutralization assays are sufficient to confer protection against HPV pseudovirion genital infection in recipient mice [143]. While the effect may not be as pronounced for most L2 immune sera, the study provides further conviction that the standard in vitro neutralization assay actually de-emphasizes protective antibody titers.…”
Section: L2 Vaccine Developmentmentioning
confidence: 82%